1985
DOI: 10.1088/0022-3727/18/1/013
|View full text |Cite
|
Sign up to set email alerts
|

Increase of Schottky barrier height at GaAs surfaces by carboxylic acid monolayers and multilayers

Abstract: Studies of GaAs photodiodes are described. It is shown that the introduction of a carboxylic acid monolayer between the GaAs and the Au top electrode can increase diode efficiency by up to a factor of 1.24. Further increases can be obtained by the introduction of two further layers using the Langmuir-Blodgett technique.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

1985
1985
2014
2014

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…247 The use of Langmuir-Blodgett films also offers the option to add a uniform dipole layer to the semiconductor surface. 248,249 Ideally, the potential drop generated across a uniform layer of dipolar molecules is derivable from the Helmholtz model as 250 …”
Section: A Sbh Modification With Molecular Dipolesmentioning
confidence: 99%
“…247 The use of Langmuir-Blodgett films also offers the option to add a uniform dipole layer to the semiconductor surface. 248,249 Ideally, the potential drop generated across a uniform layer of dipolar molecules is derivable from the Helmholtz model as 250 …”
Section: A Sbh Modification With Molecular Dipolesmentioning
confidence: 99%
“…They also made Au/GaAs diodes with LB layers of stearic acids (thickness 2.4 nm) and perfluorodecanoic acids (thickness 1.7 nm) and found a similar effect on the barrier height. Therefore, they concluded that the surface density of dipoles is the major parameter rather than the insulator (alkyl chain) length . The major role of interfacial electrostatics is being appreciated more and more in understanding Schottky barriers and especially in the area of organic light emitting diodes (OLEDs) .…”
Section: Introductionmentioning
confidence: 99%
“…The experimental procedure followed was in general identical with that described in our 0022-37271851122483 + 05 $02.25 0 1985 The Institute of Physics earlier paper (Tredgold and El-Badawy 1985). However, as we were using polymer films, it was necessary to maintain the sub-phase at a temperature of 30 "C to obtain sufficient fluidity of the spread monolayer and a solvent of ethyl acetate rather than nhexane was employed.…”
Section: Methodsmentioning
confidence: 99%
“…In a recent paper (Tredgold and El-Badawy 1985) we showed that it is possible to increase the efficiency of a solar diode based on GaAs by a factor of 1.24 by the insertion of an insulating Langmuir-Blodgett layer between the semiconductor and the top electrode. The technique of inserting a thin insulating layer into a Schottky solar diode was originated by Stirn and Yeh (1975) and has been studied in the context of GaAs by van Meirhaeghe er a1 (1980,1983).…”
Section: Introductionmentioning
confidence: 99%